Hartmann’s Procedure Versus Primary Anastomosis with Protective Proximal Stoma after Distal Colon Resection and Anterior Rectal Resection in Elective and Delayed Surgical Interventions - V. Z. Totikov; Z. V. Totikov; D. V. Toboev; R. A. Khallaev (Креативная хирургия и онкология, 2025)
Introduction. The optimal completion strategy for surgical interventions following resection of the distal colon and proximal rectum in elective and delayed operations remains a subject of active scientific debate, particularly in patients with perifocal abscesses, pelvic inflammatory disease, or inadequate preoperative bowel preparation. Aim. This study aims to compare the outcomes of Hartmann’s procedure, distal colon resection, and anterior resection of rectum with primary anastomosis and protective stoma in patients with the compensated and chronic forms of colonic obstruction, perifocal abscesses, the hypertrophy of anastomosed segments, and unsatisfactory preoperative bowel preparation. Materials and methods. The study included 97 patients. Group 1 comprised 43 patients who underwent Hartmann’s procedure. Group 2 included 54 patients who received either distal colon resection or anterior resection of rectum with primary anastomosis and protective stoma (preoperatively or during surgery). Results and discussion. Postoperative mortality was 2.3% in Group 1 and 1.8% in Group 2. Postoperative complications occurred in 13.9% and 16.7% of cases, respectively. Reconstructive operations were carried out in 79.1% of patients in Group 1 versus 100% in Group 2. Furthermore, Group 1 exhibited a higher incidence of inflammatory complications (21.1%) compared to Group 2 (15.1%). Conclusion. A primary anastomosis with a protective proximal stoma demonstrates comparable rates of anastomotic leakage, inflammatory complications, and mortality to Hartmann’s procedure in patients with colon tumors complicated by compensated intestinal obstruction, perifocal abscesses, and unsatisfactory preoperative bowel preparation (fecal contamination). Furthermore, the reconstructive phase following primary anastomosis is technically less complex and less traumatic, offering reduced surgical complexity and invasiveness.